The Effect of Shoots Number on Upper Stem and Length of Lower Stem on The Success of Mango Plants Grafting - Ayu Fitrisia, Aulia; Rinie Pratiwi Puspitawati,; Ahmad Bashri, (LenteraBio : Berkala Ilmiah Biologi, 2024)
Mango is one of the horticultural crops that has the potential to be developed in Indonesia. Fulfillment of the increasing availability of mango is done by grafting. This study aims to determine the growth of the connection results which include stem length, stem diameter, length of shoots break, number of leaves, anatomy of the connection union, and percentage of success. The experimental research used a two-factorial group randomized design with treatment combinations consisting of E1B1, E1B2, E1B3, E2B1, E2B2, E2B3, E3B1, E3B2, E3B3. Data were analyzed using descriptive statistics. The results showed that there was no interaction between the number of scion shoots and rootstock length on all parameters observed. The treatment combination with the number of scion shoots 4-5 and rootstock length 30-35 cm produced the best percentage of grafting success. The anatomical structure of the connection treatment combination influenced the tissue attachment. A less than optimal connection is characterized by differences in the shape and size of the vessel network on the rootstock which is larger than the scion. Optimal connectioning is characterized by the same shape and size of the vessel network circles on the scion and rootstock.